2009
DOI: 10.1577/t08-175.1
|View full text |Cite
|
Sign up to set email alerts
|

Egg Size Variation in Lake Trout: Phenotype–Habitat Correlations Show an Effect of Rearing Environment

Abstract: Our objective was to evaluate how different lake environments (Laurentian Great Lakes versus inland lakes) and hatchery rearing influence egg traits in lake trout Salvelinus namaycush. Lake trout eggs were collected from 11 hatchery populations and 15 wild populations in the vicinity of the Great Lakes. Average egg size (controlling for body size) differed among populations but not between hatchery and wild populations or Great Lakes and inland lake populations. However, within-female egg size variability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(34 reference statements)
2
9
0
Order By: Relevance
“…The prevalence of positive maternal effects on egg size in this species, in concert with similar relationships between egg size and maternal size in other species such as yellow perch ( Perca flavescens ; Andree et al. ), lake trout (Jastrebski and Morbey ), and Atlantic cod ( Gadus morhua ; Marteinsdottir and Steinarsson ), suggests that management practices protecting large, old females could indeed improve stock stability and productivity (Hixon et al. ).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The prevalence of positive maternal effects on egg size in this species, in concert with similar relationships between egg size and maternal size in other species such as yellow perch ( Perca flavescens ; Andree et al. ), lake trout (Jastrebski and Morbey ), and Atlantic cod ( Gadus morhua ; Marteinsdottir and Steinarsson ), suggests that management practices protecting large, old females could indeed improve stock stability and productivity (Hixon et al. ).…”
Section: Discussionsupporting
confidence: 58%
“…Similar to this study, variance in offspring length was negatively correlated with maternal age and clutch number in Daphnia magna (Ebert ). Other examinations of intra‐individual offspring size variation in fish (Einum and Fleming ) have found generally low amounts of variation and little evidence for environmental correlates, instead suggesting that observed variance within clutches may be simply due to a lack of precise control of egg size by individual females (Jastrebski and Morbey ). However, the relationship of egg size CV to maternal length among populations and seasonal thermal conditions within populations suggests that such variation is not simply random variance and merits further examination, as variation in offspring size has important potential implications for offspring fitness, especially in unpredictable environments or where intraspecific competition is prevalent (Parichy and Kaplan , Koops et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a negative relationship between egg size and fecundity has been detected in many species (e.g., Dziminski et al, 2009;Heath et al, 1999), including our study species, walleye (Sander vitreus; Henderson and Nepszy, 1994). Moreover, past studies have demonstrated linkages between egg size and egg quality (e.g., Jastrebski and Morbey, 2009;Murry et al, 2008;Wiegand et al, 2004), offspring size, and hence, offspring performance (Miller et al, 1988). For example, larger walleye eggs tend to have greater yolk and oil volumes (Moodie et al, 1989), and even though proportional lipid content may be independent of egg size (Czesny et al, 2005), total lipid content will increase with egg size.…”
Section: Introductionsupporting
confidence: 50%
“…Egg size remains an interesting parameter to measure. Although the possible benefit effect of egg size on egg survival and alevins is still debated, especially under aquaculture conditions (Bobe and Labbé, 2010; Bromage et al, 1992; Campbell et al, 1992; Jastrebski and Morbey, 2009; Migaud et al, 2013; Springate and Bromage, 1985b), it is established that larger eggs produced larger alevins (Springate and Bromage, 1985) with substantial fitness advantages over small alevins (Heath et al, 2003). While egg size is very often measured in studies on fish reproductive performance, it is unusual to observe egg size variability in intra spawn as a measured parameter.…”
Section: Resultsmentioning
confidence: 99%